Can index insurance alter pastoralists' labor allocation decisions? Evidence from East Africa - Sakketa, Tekalign Gutu; Kornher, Lukas (Journal of the Agricultural and Applied Economics Association, 2025)
Social protection programs designed to reduce the impact of economic, climatic, and social shocks on vulnerable livelihoods are becoming more popular. This study explores the causal effects of index‐based livestock insurance (IBLI) programs that have been implemented among pastoralists in Ethiopia and Kenya. Our findings indicate that IBLI coverage influences household labor allocation by prompting shifts and expansions in agricultural production, leading to more diversified livelihood activities both on and off‐farm in both countries. These findings have significant policy implications for promoting the diversification and transformation of livelihood options for households in drought‐prone regions.